The political economy of interstate conflicts and industrial development - Helge Zille (University of Copenhagen, Department of Economics, 2022)
This PhD thesis consists of three self-contained chapters within the fields of international and development economics. Chapter 1: The Role of Labor Composition and Quality in Determining the Productivity-Wage Gap: Evidence from Industrial Zones in Myanmar - with John Rand, Finn Tarp, and Neda Trifkovi'c The first chapter uses a large nationally representative survey of private manufacturing enterprises to estimate productivity and wage gains associated with industrial zones in Myanmar. Moreover, we investigate the contribution of the industrial zones in facilitating agglomeration and human capital returns to firms and workers. Our results show that being located in an industrial zone is associated with higher value added per worker, but the extent to which this is reflected in worker wages depends on the labor force composition. Productivity gains related to agglomeration and hiring of trained workers are larger in industrial zones than elsewhere. While increasing the share of women workers can lead to short-term productivity losses, our estimates show that worker wages improve in firms with a higher share of women workers. Our results highlight the role of labor force quality and composition in affecting the firm performance, but also illustrate that the benefits from industrial zones extend beyond agglomeration, bringing out the advantages of planned industrial zones as opposed to relying on innate industrial clustering. [...]
Keywords: 330